Effect of fluorine addition on transparent and conducting Al doped ZnO films - Kim, Inho; Lee, Kyeong-Seok; Lee, Taek Seong; Jeong, Jeung-hyun; Cheong, Byeong-ki; Baik, Young-Joon; Kim, Won Mok (AMER INST PHYSICS, 2006)
Al doped ZnO (AZO) films with varying fluorine content were prepared by radio frequency magnetron sputtering at a room temperature to investigate doping effects of fluorine on the structural, the optical, and the electrical properties. The small amount of fluorine addition to AZO films resulted in beneficial effect on the electrical conductivity by improving the direct current (dc) Hall mobility, and the minimum specific resistivity was as low as 5.9x10(-4) Omega cm. With increasing fluorine content in AZO films, the optical absorption loss in the visible range decreased regardless of carrier concentration in the films. X-ray diffraction and scanning electron micrograph analyses showed that the crystallinity of AZO films was deteriorated by addition of fluorine. Small amount of fluorine addition to AZO film resulted in decrease of absorption loss as well as increase in Hall mobility, and the beneficial effects of fluorine addition was deduced to be caused by killing in-grain point defects. From the comparison between the dc Hall mobility and the optical mobility, it was concluded that fluorine excessively added to AZO increased grain boundary scattering, which was explained using two phase model rather than charge trapping model. (c) 2006 American Institute of Physics.
Keywords: THIN-FILMS; DEPOSITION